Periodontitis aggravates pulmonary fibrosis by Porphyromonas gingivalis-promoted infiltration of neutrophils and Th17 cells - Ye, Hui-Lin; Meng, Xiao-Qian; Li, Huxiao; Sun, Xiaoli; Lin, Wen-Zhen; Zhou, Lu-Jun; Zhang, Jun; Hou, Chenchen; Xu, Shuo; Chen, Bo-Yan; Qiu, Che; Li, Yu-Lin; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionIdiopathic pulmonary fibrosis (IPF) is a fatal interstitial lung disease. However, the pathogeny of IPF is poorly understood, and therapeutic options are very limited. Periodontitis (PD) is a chronic inflammatory disease that leads to dysbiosis of both the oral microbiome and host immune responses. While previous studies have suggested a PD-IPF association, insights into the mechanisms remain limited.MethodsThe PD mouse model was established by the ligation of molars and oral inoculation of subgingival plaques from PD patients and subsequently incorporated with a bleomycin-induced pulmonary fibrosis model. The effect of PD on pulmonary fibrosis was determined. Changes of immune cells were analysed using flow cytometry. Moreover, the microbiome changes of the lungs and oral cavity were assessed by 16S rRNA gene sequencing and fluorescence in situ hybridization. Finally, the effect and mechanism of the specific PD pathogen on pulmonary fibrosis were determined.ResultsPD significantly aggravated pulmonary fibrosis in mice by increasing the infiltration of neutrophils and Th17 cells. Neutrophils and Th17 cells are critical in PD-induced aggravation of pulmonary fibrosis, and Th17 cells regulate neutrophils via IL-17A. The PD pathogen Porphyromonas gingivalis (Pg) was detected enriched in both the oral cavity and lungs. Pg was further determined to exacerbate pulmonary fibrosis by increasing the expansion of neutrophils and Th17 cells in mice.ConclusionPD aggravates pulmonary fibrosis in mice, which is likely induced by Pg-promoted infiltration of neutrophils and Th17 cells. Treatment targeting PD or Pg might be a promising strategy to clinically ameliorate IPF.